2010
DOI: 10.3109/08958370903161232
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metal compounds with distinct physicochemical properties on iron homeostasis and antibacterial activity in the lungs: chromium and vanadium

Abstract: In situ reactions of metal ions or their compounds are important mechanisms by which particles alter lung immune responses. We hypothesized that major determinants of the immunomodulatory effect of any metal include its redox behavior/properties, oxidation state, and/or solubility, and that the toxicities arising from differences in physicochemical parameters are manifest, in part, via differential shifts in lung iron (Fe) homeostasis. To test the hypotheses, immunomodulatory potentials for both penta-valent v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Specifically, V V has a significant local effect, causing significant increases in cytokines, which may help explain the toxic effects of these metals when they are inhaled (Ghio and Cohen, 2005;Prophete et al, 2006;Cohen et al, 2010). It has been reported that the exposure of human bronchial epithelial cells to residual oil fly ash containing V, Ni and Fe produces significant increases in IL-8, IL-6 and TNF-a (Carter et al, 1997) and that the phosphorylation of MAPK proteins may mediate the metal-induced expression of inflammatory proteins in these cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, V V has a significant local effect, causing significant increases in cytokines, which may help explain the toxic effects of these metals when they are inhaled (Ghio and Cohen, 2005;Prophete et al, 2006;Cohen et al, 2010). It has been reported that the exposure of human bronchial epithelial cells to residual oil fly ash containing V, Ni and Fe produces significant increases in IL-8, IL-6 and TNF-a (Carter et al, 1997) and that the phosphorylation of MAPK proteins may mediate the metal-induced expression of inflammatory proteins in these cells .…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of oxidative stress is associated with an inflammatory response. Vanadium exposure has been related with cytokine production (Dye et al, 1999), inflammatory changes in the upper and lower respiratory tracts (Pierce et al, 1996;Cohen et al, 2010) and lung tumours (Assem and Levy, 2012). However, other authors have suggested that V may mediate the inhibition of different forms of cancer (Das et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Water-insoluble particles like V 2 O 5 are ingested by resident alveolar macrophages. Once in a macrophage phagosome, the particles undergo slow dissolution which generate free ions that can potentially exit the cells, then enter/cross through epithelial cells and ultimately into erythrocytes, and so become a part of the generic circulation (Cohen et al 2010). It is these latter now-solubilized forms of vanadium to which NK cells are most likely exposed in situ (Roberts et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Ghio and Cohen (2005) have theorized that the immunomodulatory effect of particulate matter, such as welding fume, may involve a disruption of Fe homeostasis in cells and tissues. It is possible that other metals may compete with Fe so that lung phagocytes become Fe-insufficient and unable to function properly, while simultaneously allowing for greater free Fe to remain available for pathogens (Cohen et al, 2010). A subsequent study by Palmer et al (2006) revealed that, surprisingly, despite high Fe loads and a low unsaturated Fe-binding capacity in sputum, no overt inflammatory response was found in blood or sputum of welders with a median employment of 10 years.…”
Section: Human Immunotoxicity Studiesmentioning
confidence: 99%